Correlation of newer inflammatory markers in patients with type 2 diabetes mellitus: A cross-sectional study - Swetha Akkina; Srikanth Akula; Rajeev Gandham; Preethi Batakala; Bhagyalakshmi Atla; Divija Reddy Bonthu; Sunkara Uha Priya (Asian Journal of Medical Sciences)
Background: Globally, diabetes mellitus (DM) is a major health concerns and has reached alarming levels. DM is a group of metabolic disorders characterized by hyperglycemia leading to micro- and macro-vascular complications. Chronic low-grade inflammation is associated with the pathophysiology of DM.